Working towards a toxic free future: the chemicals and health toolkit - Women in Europe for a Common Future, Utrecht (Utrecht, 2004)
"Chemicals are all around us, not only in laboratories and in the emissions of heavy industry, but also in our homes. They are in many of the products we use in our daily lives. As consumers of goods, women make many decisions about what they will purchase and bring into their homes. We believe that women have the right to know about which toxic chemicals are found in the products they use, what concentrations they are present in, and the effects of those chemicals on their health and environment. The more they know, the better equipped they will be to demand the truly safe standards from their policy makers and producers of goods. An important aspect of the "right to know" is the clear labelling of products. It is almost impossible for the average citizen to know everything about the list of ingredients on a label. However, clear labelling with easy to understand information and hazard warnings are very important if consumers are to be empowered to make informed decisions This chapter highlights some areas where toxic chemicals might be present in households, and how consumers can reduce their risks. Please note that while this chapter gives a lot of examples, it does not give a complete overview of all the toxic chemicals in a household. For instance, while some of the risky chemicals found in paint are discussed in this chapter, not all of them are listed. Furthermore, if you happen to use wallpaper, a whole new set of chemicals would be involved. We encourage you to look deeper into the issues that interest you the most, and use the list of contacts at the end of the chapter as you begin your search."